A NARRATIVE INQUIRY INTO MIDWIFERY EFL STUDENTS’ EXPERIENCES USING CANVA: CHALLENGES AND ADAPTATIONS IN ONLINE SPEAKING CLASSES - Rina Wahyuni; Yulia Wahyuningsih (Universitas Muhammadiyah Metro, 2025)
This study explores the effectiveness of Canva as a learning tool to increase the English-speaking skills of midwifery students, focusing on their experiences, challenges, and adaptations in online speaking classes. Speaking is a vital skill for academic and professional communication, yet many students struggle due to low confidence and limited practice opportunities. The research aims to evaluate students' views on using Canva to enhance their speaking skills. A qualitative narrative inquiry was conducted, supplemented by a closed-end questionnaire to capture students’ perceptions, with responses summarized descriptively. The findings reveal that Canva’s interactive features significantly increased students' speaking confidence and engagement in EFL classrooms. Additionally, the study suggests that Canva’s flexibility allows students to practice speaking anytime and anywhere, making it an effective tool for enhancing speaking proficiency. The integration of Canva into English language teaching holds potential for improving language skills while fostering creativity and self-expression. The results of this study suggest that Canva be incorporated into language learning curricula to maximize students’ speaking potential and motivation. These findings provide insights for EFL instructors and curriculum developers to design more engaging and supportive online speaking environments.